Effect of soil suction on soil microbial activity - Syazwina Zafira, Zamanuddin (2015)
In Malaysia, the total oil palm acreage rises from year 1970-2000. Palm oil mill effluent (POME) is a residual liquid waste product obtained after extraction of soil from the fruits of oil palm and has high content of nutrients, total solids, total suspended solids that causes pollution. Palm oil mill generated huge POME with an average of 53 million m3 and is poured away into available land near the mill. By using soil microbial, it is able to treat the contaminated soil that is caused by POME. However, soil bacteria can only survive in an optimum condition, thus, the water content in the soil should be determined. Therefore, two samples of soil, (i) uncontaminated soil (ii) contaminated, are tested with different suctions by using Vapour Equilibrium Technique to find the optimum water content and suction for the soil microbial to survive. In order to check the reduction of contaminants which is Carbon (C) in the contaminated soil, the initial and final total organic carbon (TOC) of contaminated soil is recorded. The identification of the soil bacteria is by using Spread Plate Method. The test is conducted on the uncontaminated soil to identify the fungi and bacteria that digested the carbon in the soil. Based on the results, there is a reduction of the contaminant in the polluted soil by 3.884 mg/L. The optimum water content and suction for the soil bacteria to make it able to reduce the contaminant is 83.49% and 10.58 MPa respectively. Therefore, the soil microbial is able to treat contaminated soil caused by POME with an applied suction of 10.58 MPa and an optimum water content of 83.49%.